Effect of a call recall system on uptake of cervical cancer screening among non compliant school teachers in Kuala Lumpur / Fauziah Abdullah - Abdullah, Fauziah (2013)
Introduction: The Pap smear has been regarded an important cervical screening tool since the 1940s. However, women’s adherence to screening practices remains unsatisfactory, especially in developing countries. Indeed, the significance of the Pap smear has been overlooked by beneficiaries in Malaysia. Therefore, cervical cancer remains a major public health problem. An opportunistic cervical screening programme was introduced in Malaysia in the 1960s. However, Pap smear coverage is still unsatisfactory, underlining the need to implement an alternative approach. The aims of this study are to determine the effect of a call-recall system regarding Pap smear practices among non-compliant school teachers and to explore both women’s and provider’s perceptions about different cervical screening programmes.